Trends in beekeeping and honey bee colony losses in Latin America - Requier, Fabrice (2018)
Over the past decade, several countries have carried out monitoring programs of managed honey bee colonies, which suggest beekeeping difficulties, with high colony loss rates all over the world. Although Latin America plays a major role in the global honey supply, information about trends in beekeeping activities and honey bee colony losses are lacking. Using the Food and Agriculture Organization of the United Nations (FAO) dataset and a synthesis of unpublished data of colony losses survey carried out over the last 7 years, we reveal a worrying situation of the beekeeping in this region. The Latin American trends in honey production and beehive numbers are drifting from the global pattern, and several high colony loss rates were registered in this region. These results reveal the presence of beekeeping difficulties in Latin America. However, the variability in methods of colony loss survey across initiatives prevent proper conclusion on loss rates. Efforts are needed to adapt, centralize and standardize methods to monitor honey bee health and colony losses across countries in Latin America, the main objective of the “colony losses” working group at the LatinAmerican Society for Bee Research, SOLATINA, a large-scale platform created in 2017 to coordinate bee research programs in Latin America.